2015
DOI: 10.1111/psyp.12593
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for microsaccadic artifacts in the EEG using independent component analysis and beamforming

Abstract: Article:Craddock, M, Martinovic, J and Müller, MM (2016) Accounting for microsaccadic artifacts in the EEG using independent component analysis and beamforming. Psychophysiology, 53 (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In the visual domain, earlier work on basic stimuli, investigating GBRs to coherently (i.e., parallel) vs. incoherently moving bars (Gray and Singer, 1989; Gray et al, 1989; Engel et al, 1991a,b) in animals was closely followed by cognitive investigations, with real object pictures eliciting greater GBRs than pictures of unrecognizable, fragmented or scrambled objects or faces (Tallon-Baudry et al, 1996; Gruber et al, 2002; Henson et al, 2009; Hassler et al, 2011; Bertrand et al, 2013; Gao et al, 2013; Craddock et al, 2015). Although, Yuval-Greenberg and colleagues (Yuval-Greenberg et al, 2008) showed that induced gamma-band activity (iGBA) in neurophysiological data can be contaminated by artifacts originating from miniature saccades or muscle activity, we note that: (1) several of these results can hardly be attributed to effects of microsaccades, as, for example, these studies controlled for the physical features of the stimuli (Gruber et al, 2002), presented stimuli tachistoscopically so that eye movements were discouraged or excluded muscle artifacts based on EMG recordings (Pulvermüller et al, 1997), or used intracortical recording methods (or magnetoencephalography, MEG) (Bertrand et al, 2013; Gao et al, 2013), which are minimally affected by small eye artifacts; (2) some evidence suggests that microsaccades actually decrease when looking at a coherent stimulus as compared to an incoherent one (Makin et al, 2011); and (3) the use of artifact-removing methods such as independent component analysis and beamforming (Keren et al, 2010; Craddock et al, 2016) enables identifying iGBA activity increases in the signal even after removal of miniature-saccade effects (Hassler et al, 2011, 2013; Craddock et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In the visual domain, earlier work on basic stimuli, investigating GBRs to coherently (i.e., parallel) vs. incoherently moving bars (Gray and Singer, 1989; Gray et al, 1989; Engel et al, 1991a,b) in animals was closely followed by cognitive investigations, with real object pictures eliciting greater GBRs than pictures of unrecognizable, fragmented or scrambled objects or faces (Tallon-Baudry et al, 1996; Gruber et al, 2002; Henson et al, 2009; Hassler et al, 2011; Bertrand et al, 2013; Gao et al, 2013; Craddock et al, 2015). Although, Yuval-Greenberg and colleagues (Yuval-Greenberg et al, 2008) showed that induced gamma-band activity (iGBA) in neurophysiological data can be contaminated by artifacts originating from miniature saccades or muscle activity, we note that: (1) several of these results can hardly be attributed to effects of microsaccades, as, for example, these studies controlled for the physical features of the stimuli (Gruber et al, 2002), presented stimuli tachistoscopically so that eye movements were discouraged or excluded muscle artifacts based on EMG recordings (Pulvermüller et al, 1997), or used intracortical recording methods (or magnetoencephalography, MEG) (Bertrand et al, 2013; Gao et al, 2013), which are minimally affected by small eye artifacts; (2) some evidence suggests that microsaccades actually decrease when looking at a coherent stimulus as compared to an incoherent one (Makin et al, 2011); and (3) the use of artifact-removing methods such as independent component analysis and beamforming (Keren et al, 2010; Craddock et al, 2016) enables identifying iGBA activity increases in the signal even after removal of miniature-saccade effects (Hassler et al, 2011, 2013; Craddock et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Previous co-registration studies have shown that despite their small size, miniature saccades can generate sizable eye muscle (Craddock et al, 2016;Yuval-Greenberg & Deouell, 2009) and brain potentials (Dimigen et al, 2009;Gaarder et al, 1964;Meyberg et al, 2015) in EEG. Furthermore, because the amplitude and rate of miniature saccades often differs systematically between experimental conditions (Rolfs, 2009), these additional signals can seriously distort stimulus-locked analyses in the time and frequency domain (Dimigen et al, 2009;Yuval-Greenberg et al, 2008).…”
Section: Experiments 1: Face Perceptionmentioning
confidence: 99%
“…Although some residual artifacts (in particular from spike potentials) are visible in the waveforms of most published FRP studies, it seems likely that correction procedures can be improved further in the future, for example, by taking into account the information provided by the eye-tracker. Specifically, the concurrent eye-tracking data is useful to select optimal training data for the ICA algorithm (Craddock, Martinovic, & Müller, 2016;Keren et al, 2010), to identify artifact components (Plöchl et al, 2012), and to evaluate the results of the correction (Dimigen, 2020;Ries et al, 2018b). Recent findings indicate that if ICA procedures are fine-tuned for free viewing experiments in this manner, ocular artifacts can be almost fully removed with relatively little distortion of genuine brain activity (Dimigen, 2020;Ries et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…during attempted fixation generate sizeable SPs (Armington, 1978;Dimigen, Valsecchi, Sommer, & Kliegl, 2009;Yamazaki, 1968;Yuval-Greenberg, Tomer, Keren, Nelken, & Deouell, 2008), which introduce a broad band artifact in the time-frequency spectrum of the EEG, affecting the low-amplitude beta and gamma bands, in particular (Reva & Aftanas, 2004;Yuval-Greenberg et al, 2008). Complete removal of SPs with ICA has proven challenging even for microsaccades (Craddock, Martinovic, & Müller, 2016;Hassler, Barreto, & Gruber, 2011;Hipp & Siegel, 2013;Keren et al, 2010) and ICA often fails to single out the SP in one or more distinct ICs (Hipp & Siegel, 2013;Keren et al, 2010). In addition, even clean SPs components can be difficult to spot in scalp maps (inverse weights), especially if EOG electrodes were not placed around both eyes, recorded with a bipolar montage, or excluded before ICA.…”
Section: Spike Potentials Have Received Attention Because Even Involumentioning
confidence: 99%